Pengaruh Bauran Pemasaran Terhadap Volume Penjualan Di AOI Ramen Bandung - Widaningsih, Imas Sri; Fatihah, Dian Candra (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research to find out the influence the marketing mix has on sales volume. This research use saturated sampel which is 30 respondents who were consumers of AOI Ramen Bandung and uses quantitative methods by collecting data using a questionnaire. This research obtained the results of the correlation coefficient value of 0.863, which means that the Marketing Mix has an influence on sales volume with a moderate category, which is in the range of 0.6-0.7. From the t hypothesis test, it shows that the value of t count against t table is 0.691> 0.361, which means that it is accepted and has an effect on sales volume. Meanwhile, from the coefficient of determination, the R square value is 42%, which means that if the marketing mix goes well, it will increase the sales volume by 42%, while the remaining 58% is influenced by other components not examined by the author. The obstacles faced by AOI Ramen Bandung are getting raw materials for making noodles and other toppings that are getting scarce and expensive. The solution that can be given to AOI Ramen Bandung is to look for local raw materials at a more affordable price, so as not to make the taste of Ramen at AOI Ramen Bandung change.